2016
DOI: 10.1073/pnas.1605997113
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition enhances antimicrobial peptide but not inflammatory cytokine expression upon bacterial challenge

Abstract: Antimicrobial peptides (AMP) are defense effectors of the innate immunity playing a crucial role in the intestinal homeostasis with commensals and protection against pathogens. Herein we aimed to investigate AMP gene regulation by deciphering specific characteristics allowing their enhanced expression among innate immune genes, particularly those encoding proinflammatory mediators. Our emphasis was on epigenetic regulation of the gene encoding the AMP β-defensin 2 (HBD2), taken as a model of possibly specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 43 publications
4
58
1
Order By: Relevance
“…Whether this is due to immunologic or metabolic shifts, such as changes in bile acid biosynthesis, must be considered in future studies. That HDAC6 affects regulation of antimicrobial peptides (13,74) implies that innate immunity also may be involved. The commonality between early-life male and female pups showed that the later differences did not originate from inheritance of different bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Whether this is due to immunologic or metabolic shifts, such as changes in bile acid biosynthesis, must be considered in future studies. That HDAC6 affects regulation of antimicrobial peptides (13,74) implies that innate immunity also may be involved. The commonality between early-life male and female pups showed that the later differences did not originate from inheritance of different bacterial communities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the increase in expression of PML and ATRX we observed following HDACi treatment may reflect a specific regulation of this part of the immune response. Interestingly, inhibition of HDAC by TSA dramatically enhanced induction of antimicrobial peptides but not of proinflammatory cytokines (Fischer et al, 2016), further indicating selective expression post HDACi treatment of different parts of the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…Histone acetylation induces the expression of innate-immunity genes encoding products such as AMPs (but not inflammatory cytokines) in cells challenged with E. coli (42). We found that insects can selectively express AMPs and cytokine-like proteins when challenged with UPEC and ABU strains.…”
Section: Discussionmentioning
confidence: 78%